2015
DOI: 10.1016/j.egypro.2015.03.250
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recycling of Human Excreta to Energy through Biogas Generation: Indonesia Case

Abstract: The use of waste to produce biogas not only limited to the waste from nature such as agricultural waste, food waste, or cattle manure; but can also use human waste hereinafter called human excreta. The use of human excreta for biogas generation considered beneficial either in the term of process or environment. It is at the same time produce energy and reducing environmental problem that caused by unmanaged human excreta disposal. In Indonesia, the main use of biogas itself is for cooking and generating electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 1 publication
0
32
0
1
Order By: Relevance
“…The following parametres are used in the study. Total dry matter mass of daily waste produced = 0.35 x 348kg = 121.8kg According to Buswell, Carbon content of dry matter in the human waste = 24% Total carbon content in the total human waste produced per day = 0.24 x 121.8 kg =29.23 kg From table above, the% biodegradability of human waste is 60% for volatile solids and 50% for total solids [18] Assuming volatile solids. The mass of biodegradable matter = 0.6 x 29.23 kg = 17.54 kg (this is the carbon that will be converted to Biogas).…”
Section: Methodsmentioning
confidence: 99%
“…The following parametres are used in the study. Total dry matter mass of daily waste produced = 0.35 x 348kg = 121.8kg According to Buswell, Carbon content of dry matter in the human waste = 24% Total carbon content in the total human waste produced per day = 0.24 x 121.8 kg =29.23 kg From table above, the% biodegradability of human waste is 60% for volatile solids and 50% for total solids [18] Assuming volatile solids. The mass of biodegradable matter = 0.6 x 29.23 kg = 17.54 kg (this is the carbon that will be converted to Biogas).…”
Section: Methodsmentioning
confidence: 99%
“…On a design experiment scale, Nisa (2015) has researched the addition of bran for the production of biogas in the wastewater treatment plant. (Andriani et al, 2015) showed that the application of biogas using human excreta provided alternative energy source and helped the environment while sludge itself could be piped to the fish pond or further processed into fertilizer. The investment of private sector in wastewater management is also recommended.…”
Section: Socialmentioning
confidence: 99%
“…Ini berarti bahwa jumlah nitrogen lebih besar dari pada jumlah karbon, yang mengakibatkan banyak pembentukan amonia dari proses dekomposisi dan selanjutnya meningkatkan pH sistem menjadi basa. Untuk mengatasi kekurangan ini, penambahan bahan baku C/N ratio tinggi sangat dibutuhkan seperti jerami padi (rasio C/N 12,5-25), sekam padi (rasio C/N 100-125), atau tongkol jagung (rasio C/N 50) [7].…”
Section: Ukuran Digester Biogasunclassified